School Plant Facility and Maintenance: A Necessity Effective Teaching and Learning in Technical Vocational Education and Training - Jane Itohan Oviawe; David OMOH; Uwameiye (Journal of Education and Vocational Research, 2019)
Since Technical Vocational Education and Training (TVET) is all about skill acquisition in order to prepare learners to fit into the world of work and become self- reliant, the curriculum for such training has to involve the use of adequate provision of necessary fa c il ities c all ed s chool plant in order to ac hieve effective teaching and learning. The purpose of this paper is to affirm the need for adequate facilities in a Technical and Vocational Institution, and the necessity to have a good maintenance structure in place in order to achieve the desired objectives and enhance the life span of the facilities. This paper also looked a tissue of challenges facing the maintenance of these facilities in Technical and Vocational Educational institutions in Nigeria. Conclusions were made looking at suggestions in order to achieve adequacy in the provisions of facilities such as machines, workshops, equipment and tools in Technical and Vocational schools which can effectively enhance teaching and learning and by extension provide economic growth in any nation.